Pipeline Performances under Earthquake-Induced Soil Liquefaction: State of the Art on Real Observations, Model Tests, and Numerical Simulations - Massimina Castiglia; Tony Fierro; Filippo Santucci de Magistris (Shock and Vibration)
The design and the manufacture of the oil and gas pipelines are being improved over the years in response to the observed damages and related disastrous effects. The improvements are possible, thanks to the increasing knowledge about pipeline performances in specific contexts. The seismic hazard on buried pipelines has always been of major concern, and the earthquake-induced soil liquefaction effects are among the most important issues to be accounted for in the design. Experiences based on case histories, experimental modelling, and numerical simulations represent the source of understanding of the involved mechanisms, the affecting parameters, and the structure response. Recently, all these aspects are becoming more accurate, thanks to the use of monitoring systems. The protection of pipelines from the seismic hazard is a crucial and challenging issue. This paper provides an overview of the research that has been conducted over the years in the specific framework of soil liquefaction phenomenon. Case histories on pipeline performances, commonly adopted analytical methods, and results of model tests and numerical simulations are summarized with main focus on the level of knowledge achieved up to date and the existing limitations that represent open issues for further development of the research. This study represents a useful background to be adopted from academics and practitioners in order to enhance the methods of analyses of the pipelines, thus improving their performances in the applications of the oil and gas industry.